Electrochemical study of TEOS, TEOS/MPTS, MPTS/MMA and TEOS/MPTS/MMA films on tin coated steel in 3.5% NaCl solution - Sakai, R. T.; da Cruz, F. M. Di L. [UNESP]; de Melo, H. G.; Benedetti, Assis Vicente [UNESP]; Santilli, Celso Valentim [UNESP]; Suegama, P. H. (Elsevier B.V. Sa, 2012)
This work compares the anticorrosion features of siloxane layers as eco-friendly alternatives for chromium passivation process on industrials tin coated steel and unravels the influence of each component of the film. The films were prepared with synergistic blends of siloxanes as tetraethyl orthosilane (TEOS), 3-methacryloxy-propyl-trimethoxysilane (MPTS) and methyl methacrylate (MMA). To assess the influence of each component, five different films were prepared: TEOS-based, MPTS-based, TEOS/MPTS, MPTS/MMA and TEOS/MPTS/MMA. The corrosion resistance of the coatings was evaluated by means of open circuit potential, anodic polarization curves and electrochemical impedance spectroscopy measurements, and the anticorrosion properties discussed based on electrical equivalent circuit fitting. Coated surfaces were analyzed using atomic force microscopy and the coatings' thicknesses were evaluated by means of glow discharge optical emission spectroscopy. The results plainly showed the efficiency of the anticorrosion properties of the film in a 35 wt.% NaCl solution and have clearly revealed the improvement of the protective properties of the coating when the MPTS was added to the formulations, pointing this component as the main responsible for the coating anticorrosion action. The addition of MMA to the formulation led to formation of coatings with low long term anticorrosion protection, which was ascribed to the low thickness. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TEOS; MPTS; MMA; Electrochemical impedance; Corrosion